Clinical Analysis of Covid-19 Infections in Children with Cancer in A Tertiary Care Hospital in Bangladesh (Journal of Dhaka Medical College, 2021)
Background: Children suffering from cancer are more vulnerable than others. This study performed to outline the clinical characteristics and outcome of children with cancer with severe acute respiratory syndrome corona virus 2 (SARS-CoV-2) infection in Dhaka Medical College Hospital, Dhaka.Methods: Clinical data and epidemiologic history of 24 children with cancer with laboratoryconfirmed COVID-19 infection by real-time reverse transcription-PCR (RNA-PCR) were admitted in the Dhaka Medical College Hospital, Dhaka from May, 2020 to June, 2020. Clinical data and epidemiologic history of these patients were restrospectively collected and analyzed.Results: Among the 24 cases, 16 (67%)were males and 8 (33%) were females. The median age was 5 years (range 0.11–12 years). The most common symptoms were fever (11 cases, 45%) and runny nose (8 cases, 33%), cough (8 cases, 33%), 6 (24%) were asymptomatic. Acute Lymphoblastic Leukemia were the most common (50%) and second most were Wilms tumor (17%). Among the 24 cases, on admission, 17 (71%) had normal white blood cell counts, while only 2 (8%) more than 10x109/L and 5 (21%) less than 4x109/L, respectively. 16 cases (67 %) had normal neutrophil count and 7 cases (29%) had neutropenia. Lymphocyte counts were normal in 50% cases, lymphocytopenia in 10 (42%). C Reactive protein and serum ferritin raised in 19(79%) cases, D-dimer raised, prothrombin time, activated partial thromboplastin time raised in 8(33%) cases. X-ray chest was abnormal in 6 cases (25%). 16 cases (66%) received intravenous antibiotics, 5 cases (21%) needed oxygen therapy and 4 cases (17%) needed corticosteroid. Ninteen (79%) patients were discharged from hospital, 3cases (13%) were discharged on request and death was 2 cases (8%).Conclusions: Children at all ages appeared susceptible to COVID-19 and there was significant gender difference. Clinical manifestations of children’s COVID-19 cases were generally less severe than those of adult patients. Death rate is more in children with cancer than others.J Dhaka Medical College, Vol. 29, No.2, October, 2020, Page 165-170